Correction: Mangrove crab intestine and habitat sediment microbiomes cooperatively work on carbon and nitrogen cycling. - Prasert Tongnunui; Yuki Kuriya; Masahiro Murata; Hideki Sawada; Michihiro Araki; Mika Nomura; Katsuji Morioka; Tomoaki Ichie; Kou Ikejima; Kohsuke Adachi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0261654.].